Observation of the marcus inverted region for bimolecular photoinduced electron-transfer reactions in viscous media - Kumbhakar, Manoj; Manna, Arpan; Sayed, Mhejabeen; Kumar, Anil; Pal, Haridas (Journal of Physical Chemistry B, 2014)
The general observation of Marcus inverted region (MIR) for bimolecular electron-transfer (ET) reactions in different viscous media, e.g., micelles, reverse micelles, vesicles, ionic liquids, DNA scaffold, etc. has been doubted in some recent publications arguing limitations in SternVolmer (SV) analysis to account for the static and transient stages of quenching in these slow diffusing media. Thus, following a theoretical treatment based on a spherically symmetric diffusion equation coupled with conventional Marcus ET description, it has been suggested that the MIR observed in viscous media arises due to the inadequate consideration of different quenching regimes and also due to the differential excited-state lifetimes of the fluorophores used than a genuine one (J. Am. Chem. Soc. 2012, 134, 11396). However, the overall treatment in this study is severely compromised by setting the minimum solvent reorganization energy (?s) to (lambda) to similar to 0.96 eV while fitting the experimental data, which unambiguously suggests that the inversion in ET rate will never appear in the exergonicity (-Delta G(0)) range of 0.16 to 0.71 eV, as is the case for the studied ET systems. Besides, the applicability of the conventional Marcus ET model (instead of Sumi-Marcus two-dimensional ET model) in such extremely viscous media with exceptionally slow solvent response is highly debatable and perhaps is the main cause of the failure in fitting the experimental data quite satisfactorily. In the present study involving ultrafast ET quenching for coumarin derivatives by dimethylaniline donor in viscous ionic liquid media, we demonstrate clear MIR for the intrinsic ET rates, directly obtained from the ultrafast decay components of 110 ps, a time scale in which diffusion of reactants is negligible and the ET rates are either faster than or, at the most, competitive with the solvent reorganization. The appearance of MIR at ?Delta G(0) similar to-0.5 eV, significantly lower than expected from the lambda(s) value, further substantiate the nonapplicability of conventional ET description but certainly advocate for the applicability of the SumiMarcus two-dimensional ET model in such media. Moreover, no obvious correlation has experimentally been observed between the excited-state lifetimes of the coumarin derivatives and the ET rates for a large number of dyes used in the present study. On the basis of the present results and drawing inferences from reported literatures in viscous media, we conclude that not only is the appearance of MIR very genuine but also the mechanistic model necessary to account the observed facts for the bimolecular ET reactions in a viscous medium is the two-dimensional ET description, which deals with an extremely slow relaxing solvent coordinate and a fast relaxing intramolecular coordinate to describe the ET reactions.